STUDI KUALITATIF TENTANG PERAN GURU DALAM MEMBENTUK KARAKTER SISWA MELALUI PEMBELAJARAN AQIDAH AKHLAK DI MADRASAH IBTIDAIYAH RAUDLATUL HASAN - Fajar Insani, Nurul; Nuryami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore the role of teachers in shaping students’ character through Aqidah Akhlak learning at Madrasah Ibtidaiyah Raudlatul Hasan. A qualitative approach with a phenomenological design was employed to gain an in-depth understanding of character education practices. The research subjects included Aqidah Akhlak teachers, upper-grade students, and school administrators, selected through purposive sampling. Data were collected through in-depth interviews, non-participant observation, and documentation studies of instructional materials. Data analysis was conducted using the Miles and Huberman model, supported by source and method triangulation to ensure data validity.The findings indicate that teachers play a crucial role as moral role models, facilitators, and agents of character transformation by integrating values such as honesty, responsibility, and empathy into the learning process. Teachers’ exemplary behavior and contextual approaches, including the use of inspirational stories and reflective discussions, were found to be effective in fostering positive character traits among students. However, limited instructional time and the diversity of students’ backgrounds remain challenges that require specific strategies to address. This study recommends enhancing teacher training and developing a more integrated curriculum to strengthen character education. Overall, the findings emphasize the importance of the role of Aqidah Akhlak teachers at Madrasah Ibtidaiyah Raudlatul Hasan in shaping a generation with noble character grounded in moral values.